Developing English Speaking Learning Materials for Saturday English School Program - Dewi Yana (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2016)
This study aims at (1) identifying the target needs, and learning needs of students, (2) developing appropriate English speaking learning materials for grade VII students of SES Program at SMPIT ABY. This research was a research and development study consisting of seven steps: needs analysis, developing course grid, developing first draft, getting the expert judgment, trying out the materials, evaluating and revising the materials, and writing the final draft. The subjects were grade VII students of SES Program at SMPIT ABY. The data were collected using questionnaires and an interview guide. The results found that the target needs of grade VII students of SES program at SMPIT ABY are the English speaking learning materials which are related to Islamic contents. Their learning needs are related to the goal, input, setting, procedure, teachers’ role, and students’ role. Four units were developed based on the target and learning needs. The interval mean value of each task component in all units of the developed materials is between 2.52 Ẍ ≤ 3.27and 3.28 Ẍ ≤ 4.03. This indicates that, the materials are appropriate to grade VII students of SES Program at SMPIT ABY.Keywords: speaking, learning materials and saturday English school program